Design, Fabrication, and Thermal Evaluation of a Solar Cooking System Integrated With Tracking Device and Sensible Heat Storage Materials - Komolafe, Clement A.; Okonkwo, Clinton E. (Frontiers in Energy Research, 2022)
Energy need for cooking in both the rural and urban areas all over the world is increasing every day as a result of an increase in population. The consequence of global warming due to the usage of fuels such as fossil fuel, firewood, and other biomass products for cooking necessitates innovative techniques that will improve the standard of living of people. In this study, the design, fabrication, and thermal evaluation of a solar cooking system integrated with an Arduino-based tracking device and sensible heat storage (SHS) materials was investigated. During the water boiling trials with black oil sensible material(BOSHSM), the obtained maximum temperatures for water, cooking box, and sensible heat storage material at 14:00 hr when the solar radiation attained its peak value of 881.2 W/m2 were 64,52, and 54 oC, respectively, while at 14:00 hr with Black coated granite sensible heat storage material (BCGSHSM) at the solar radiation peak value of 890.4 W/m2, the maximum temperatures for water, cooking box, and sensible heat storage material were 73.5, 76, and 59 oC, respectively. The maximum cooking power and thermal efficiency obtained from the water boiling trials were 48.4 and 56.4 W, and 31.6 and 35.8% respectively. Also, the results from the cooking of edibles revealed that the cooking power values ranged between 42.5 and 58.2, while that of efficiency ranged between 34.5 and 40.3% respectively. The maximum solar radiation during the cooking trial period was 986, 975, 956, and 953 W/m2. In general, from the results, the developed solar cooking system is a viable alternative to cooking with traditional/ open burning of wood or other biomass products that pose a serious environmental and health-related threat to the people living in developing countries.